2021
DOI: 10.3389/fpsyt.2020.588781
|View full text |Cite
|
Sign up to set email alerts
|

Global Imperative of Suicidal Ideation in 10 Countries Amid the COVID-19 Pandemic

Abstract: Background: The novel coronavirus (COVID-19) has had a detrimental impact on individuals' psychological well-being; however, a multi-country comparison on the prevalence of suicidal ideation due to the virus is still lacking.Objectives: To examine the prevalence and correlates of suicidal ideation among the general population across 10 countries during the COVID-19 pandemic.Materials and methods: This was a cross-sectional study which used convenience sampling and collected data by conducting an online survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 47 publications
1
50
2
1
Order By: Relevance
“…At the time of report, Hong Kong is in the fourth wave of the COVID-19 pandemic. This long-haul battle combating against the pandemic, alongside with recurrent political instability may cause unease, anxiety and depression in the general population [ 66 ]. For example, Wong et al [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of report, Hong Kong is in the fourth wave of the COVID-19 pandemic. This long-haul battle combating against the pandemic, alongside with recurrent political instability may cause unease, anxiety and depression in the general population [ 66 ]. For example, Wong et al [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Population-level evidence of increasing suicide rates remains limited; however, emerging research illustrates that the social context of the pandemic has contributed to growing rates of suicidal thoughts (3,7,47). While some research has begun to quantitatively examine associations between suicidal thoughts and socio-demographic characteristics or COVID-19 related conditions (17,23), there is a dearth of qualitative research supporting more nuanced understandings of the experience of suicidal thinking, in particular, individuals' perspectives on contributors to suicidal thoughts in the pandemic context. As a semi-anonymous forum where users can share personal stories and receive support, Reddit data presents a unique opportunity to explore how members of an active online community are experiencing suicidal thoughts related to the pandemic, and to gain rich insights into the ways in which the pandemic context variously contributes to these experiences.…”
Section: Discussionmentioning
confidence: 99%
“…While empirical evidence regarding the association between COVID-19 and suicide mortality is limited, and considered a lagging indicator not expected to reflect actual numbers for years afterwards (15), findings from a recent systematic review of past epidemics (e.g., SARS, Ebola) support a link between virus outbreaks and suicide-related outcomes, including attempts and deaths (16). There is also a growing literature demonstrating an association between the COVID-19 pandemic and suicidal thoughts (2,7,17). For example, while in 2016, 2.5% of the general population in Canada reported suicidal thoughts in the past-year (18), the prevalence of suicidal thoughts was identified as 6% over a two week period in May 2020 (3) and 10% over a two-week period in September 2020 (19).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the suicide risk among migrants is complex, as suicidal ideation and/or suicide attempts are influenced by a myriad of socio-cultural and economic factors in both the country of origin and destination, including demographic factors such as age and gender and mental health problems including depression, anxiety, and hopelessness [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Migrant workers as a vulnerable group also experience social exclusion and mental health issues in host countries, which further lead to higher risk for suicide ideation and attempt [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the literature suggests that immigrant status is positively associated with suicide ideation and attempt [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For example, a study that investigated attempted suicides among Bhutanese refugees in the United States reported that suicide risk includes, among other factors, a lack of social welfare support (e.g., employment and resettlement difficulties, inadequate social support, family separation and frustration, and integration difficulties) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%